EFFECT OF NEURODYNAMIC SLIDER ON INCREASING HAMSTRING MUSCLE FLEXIBILITY IN RANTAYA PUTRI ALUS DANCERS - Dita Mirawati; Alinda Nur Ramadhani (Gaster, 2023)
Flexibility is ability of a joint, muscles and ligaments around it to move freely and comfortably within the maximum expected range of motion. Flexibility is influenced by many factors such as anatomical condition, gender, body mass index, age, physical activity, injury, and training experience. The hamstring muscles are primarily fast-twitch and powerful movement types, so that the hamstrings are resistant to overloading but tire quickly on excessive repetitions. Excessive activity that involves contracting the hamstring muscles will cause the hamstring muscles to experience decreased flexibility. The purpose of this study was to prove the difference in the effect of giving neurodynamic slider and neurodynamic tension on increasing hamstring muscle flexibility. The method of research is experimental research with pre-test and post-test research design with control group design. The sample in this study was 32 dancers Rantaya Putri Alus at SMK N 8 Surakarta. where Group 1 given neurodynamic sliders and group 2 given nothing. Neurodynamic slider interventions were given 3 times/week for 4 weeks. Evaluation of hamstring muscle flexibility measurements using Active Knee Extension (AKE). The result in the treatment Group 1 is p = 0.000 (p <0.05) with a mean difference of 25.56 ± 7.36 with an increase in the AKE value 18.16%. Its concluded that the intervention of neurodynamic sliders can increase hamstring muscle flexibility.